Intrusion of maxillary molar using mini-implants: A clinical report and follow-up at 5 years - Maio Pinzan-Vercelino, Celia Regina; Bramante, Fausto Silva; Gurgel, Julio de Araujo [UNESP]; Carrera Eleres Vergani, Eliane Cristina; Gregorio, Rosyane de Souza (Elsevier B.V., 2017)
This clinical report describes a straightforward alternative treatment for adult patients with extruded maxillary molars, who are reluctant to use fixed appliances and complex mechanics. The maxillary molar supereruption of a 57-year-old woman was treated using buttons bonded to the buccal and palatal surfaces of the molars, 2 mini-implants, and elastomeric chains. The intrusion was achieved in 5 months. The treatment stability was observed for 5 years after treatment.